Country Partnership Framework for the Republic of Nicaragua for the Period FY18-FY22 - World Bank Group (World Bank, Washington, DC, 2018)
Nicaragua remains one of the poorest countries in Latin America. Making a significant dent in prevailing levels of poverty and vulnerability through faster, more inclusive, and sustained growth as well as better access to quality basic services are at the core of the financial year 2018‐2022 Country Partnership Framework (CPF). To achieve the required job‐creating growth faster, the country will need to increase productivity in addition to further improving the quality of its human and physical capital. In addition, a growth acceleration will also require improved access to quality basic services underpinned by institutional capacity‐building and increased data availability.To sustain and deepen the progress realized under the FY13‐17 Country Partnership Strategy (CPS) and support the government in achieving the Twin Goals, the FY18‐22 CPF envisages support across three pillars: (i) investing in human capital, particularly for disadvantaged groups; (ii) enabling private sector investment for job creation; and (iii) improving institutions for resilience and sustainability. The CPF pays special attention to disadvantaged groups and lagging territories within Nicaragua that have not participated fully in the benefits of growth. It prioritizes interventions that target specific groups such as youth, women, subsistence farmers, and Indigenous and Afro‐descendant communities with a spatial focus on rural areas in the Caribbean and Central regions where most of the poor and extreme poor are located.The CPF builds on the foundations laid down by the previous CPS while responding to new challenges. The CPF will succeed the FY13‐17 CPS, and will focus on improving access to basic services and fostering competitiveness and productivity through improvements to infrastructure and the investment climate. The current CPF builds on these approaches while presenting three main shifts with greater emphasis on: (i) private sector‐led growth; (ii) sustainability; and (iii) governance.The FY 18‐22 CPF is informed by the FY18 SCD and supports implementation of the government’s emerging National Plan for Human Development (PNDH) (Plan Nacional de Desarollo Humano). It also reflects the GoN’s commitment to the Sustainable Development Goals (SDGs) and its responsibilities and priorities in the area of climate change mitigation and adaptation.The WBG engagement supports the GoN’s efforts to reduce poverty by accelerating economic growth, generating employment for a large share of Nicaraguans and improving access to quality basic services for the most disadvantaged.